Ti-6Al-4V fretting wear and a quantitative indicator for fretting regime evaluation. (February 2021) - Wang, Jianfei; Duan, Deli; Xue, Weihai; Gao, Siyang; Li, Shu
Fretting wear between titanium alloy components in aero engine is prevailing in the blade dovetail, the blade crown, and the damping shoulders. In this study, the fretting wear behavior of Ti-6Al-4V alloy was investigated by changing the load and displacement under a high frequency (100 Hz). To simulate the actual working conditions in aero engines, both the ball and flat samples were Ti-6Al-4V alloy. It was found that as the load increased, or as the applied displacement decreased, the fretting regime changed from gross slip regime to partial slip regime. The coefficient of friction/traction at steady stage decreased as load increased. Wear scar morphologies varied with fretting running conditions. In gross slip regime, the central area was higher than the rest region of the wear scar. In the mixed slip regime, large material accumulation could be found at both ends of the reciprocating motion. In partial slip regime, a nearly original fretting sample surface was observed in the central area and wear occurred in the edge area. Furthermore, considering the wear of the paired samples, a method based on the fretting wear scar diameter was proposed to evaluate the fretting running conditions.